B7-H3-targeted CAR-T cell therapy for solid tumors. (21st October 2022) - Li, Guangfei; Wang, Haopeng; Wu, Haitao; Chen, Jian
Abstract: Since B7-H3 is overexpressed or amplified in many types of solid tumors with a restricted expression in the normal tissues, it has been an emerging immunotherapeutic target for solid tumors. This review will focus on the structural designs of developing chimeric antigen receptors (CARs) targeting B7-H3. The expression, receptor, and function of the B7-H3, as well as a short overview of B7-H3-targeted monoclonal antibody therapy, are discussed. Finally, a detailed summary of B7-H3 redirected CAR-T and CAR-NK cell approaches utilized in preclinical models and currently ongoing or completed clinical trials are presented. It has been demonstrated that B7-H3-targeted CAR-based cell therapies were safe in initial trials, but their efficacy was limited. Employing the local delivery routes, the introduction of novel modifications promoting CAR-T persistence, and combined treatment with other standard therapies could improve the efficacy of B7-H3-targeted CAR-T cell therapy against solid tumors. Graphical Abstract: UF0001 Abstract : Cancers develop by avoiding being discovered and destructed by the immune system. Cancer immunotherapy is characterized as an approach to assist the immune system to recognize and fight cancer by using uses some substances. Chimeric antigen receptor (CAR) is a protein designed to recognize a target of interest on tumor cells, immune cells armed with which are able to treat human cancers. B7-H3 is a type I transmembrane protein overexpressed in various solid tumors but scarcely detected in normal tissues. Moreover, it is associated with a poor prognosis for many cancer patients. Therefore, we discussed the role of B7-H3 in solid tumors, and concluded it as a promising therapeutic target for CAR-based immunotherapy. A number of B7-H3 CARs have been developed and tested in recent years, but which CAR construct targeting B7-H3 works best remains uncertain. Up till now, the design of B7-H3 CARs is still controversial and challenging. Hence, we summarized and compared the designs and efficacies of B7-H3 CARs utilized in preclinical models and currently ongoing or completed clinical trials in this review, and aimed to provide a better reference for future B7-H3 CAR design.